Obstructive Jaundice Due to Hepatocarcinoma With Intraductal Growth. Report of a Successful Resection. Issue 1 (1990) - Jiménez, L. C.; Teruel, Ana; Mezquita, Susana; Martínez, J.; Colina, F.
Abstract : We present a patient with hepatocellular carcinoma causing obstructive jaundice due to intraductal growth, diagnosed intraoperatively by cholangiography and histological examination, and radically treated by left lobectomy, extrahepatic biliary tract resection and Roux-en-Y hepaticojejunostomy. Survival after operation was 13 months. Other similar cases reported in the literature are reviewed.